FIELD TESTING OF THE SMBF FLUME - Costanza Di Stefano; Gian Vito Di Piazza; Vito Ferro (Journal of Agricultural Engineering, 2007)
At first, in this paper the stage-discharge relationship of a new flume, originally proposed by Samani and Magallanez, for measuring flow discharge in open channels is reviewed. The flume is obtained inserting two semicylinders in a rectangular cross-section. Then, the results of some experimental runs carried out using horizontal flumes characterized by different values of the contraction ratio (ranging from 0.17 to 0.81) are used for determining the two coefficients of the power stage-discharge equation. Finally, the stage-discharge equation is tested using flow measurements carried out, in the period December 2004 – March 2006 in the Sicilian experimental SPA1 and SPA2 basins. Field testing of the SMBF flume is developed using discharge measurements carried out by a Khafagi-Venturi flume placed in the field measurement channel of each experimental basin.